Compliance with Section 7 (2) of the Cigarettes and Other Tobacco Products Act (COTPA) 2003, Ban of Sale of Loose Tobacco, in Karnataka: A Cross-Sectional Study. Issue 2 (March 2023) - Ezhumalai, Sinu; Shanmugam, Backiyaraj; Chand, Prabhat Kumar; Murthy, Pratima
Background: Banning smoking in public places has considerably reduced the number of smokers. However, the sale of loose tobacco encourages tobacco use. There is limited data on compliance with section 7(2) of the Cigarettes and Other Tobacco Products Act (COTPA), 2003, concerning the ban on loose tobacco sales in India. The aim of this study is to assess the compliance of section 7(2) of COTPA concerning the ban on loose tobacco sales in four selected cities of Karnataka. Methods: This community-based study used a cross-sectional design. Two neighboring cities, that is, district headquarter from North (Bidar and Vijayapura) and South (Mandya and Chikkamagaluru) Karnataka were considered for the study. A total of 207 vendors and 204 smokers were selected using time-cluster sampling. Data was collected using observation and interview methods. Semi-structured interview schedules were administered to smokers and vendors. Percentages and frequencies were used to describe the data. Results: Most tobacco vendors (92%) and smokers (91%) were unaware of the loose tobacco ban. Most smokers (76%) perceive that buying cigarettes in packets would increase smoking. Most smokers (96%) prefer to buy cigarettes in loose. The sale of loose tobacco was widely prevalent (94%) in the four surveyed cities. Point of sale of loose tobacco includes tea shops (38%), petty shops (31%), pan shops (25%), and bakeries (6%). Conclusion: There is a high degree of noncompliance with Section 7 (2) of COTPA, 2003 regarding ban on selling loose tobacco.